2018
DOI: 10.3390/nitrogen1010003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nitric Oxide (NO) in Higher Plants: An Outline

Abstract: Nitric oxide (NO) is a free radical and a component of the N-cycle. Nevertheless, NO is likewise endogenously produced inside plant cells where it participates in a myriad of physiological functions, as well as in the mechanism of response against abiotic and biotic stresses. At biochemical level, NO has a family of derived molecules designated as reactive nitrogen species (RNS) which finally can interact with different bio-macromolecules including proteins, lipids, and nucleic acids affecting their functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 74 publications
0
18
0
4
Order By: Relevance
“…This might be because of the possible role of AtWAKL10 in RNS scavenging which may be due to its many fold induction (>124) in response to CysNO. Therefore a perturbation in the function may result more nitrosative stress which ultimately results in compromised plant growth as suggested by many reports (Corpas & Palma, 2018; Lee et al, 2008; Lindermayr, 2017). The difference in response of atwakl10 plants to different NO donors might be because of the differential accumulation of intracellular NO due to different NO release rates of NO donors (He & Frost, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…This might be because of the possible role of AtWAKL10 in RNS scavenging which may be due to its many fold induction (>124) in response to CysNO. Therefore a perturbation in the function may result more nitrosative stress which ultimately results in compromised plant growth as suggested by many reports (Corpas & Palma, 2018; Lee et al, 2008; Lindermayr, 2017). The difference in response of atwakl10 plants to different NO donors might be because of the differential accumulation of intracellular NO due to different NO release rates of NO donors (He & Frost, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, nitric oxide (NO), a versatile signaling molecule has been found to play critical roles in plant defense reactions including induction of antioxidant potential under various plant abiotic stresses [ 26 , 27 ]. Adequate evidence substantiates a wide range of roles of NO in plant physiological processes including germination, photosynthesis, and defense mechanism both under normal and environmental stresses [ 28 , 29 ]. In plants, the cell-protective role of NO has been tested with DNA, proteins, lipids, and chlorophyll [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, it maintains reactive oxygen species (ROS) at low levels through changing the activities of key antioxidant enzymes (Niu and Guo, 2012;Groß et al, 2013;Ahmad et al, 2016). Various investigations have shown that NO is implicated in several hormonal and biological responses in plants (Hasanuzzaman et al, 2012;Corpas and Palma, 2018), but the likely contribution of NO to thiamine-induced antioxidant defense needs to be elucidated. Thus, this study aimed to assess if thiamineinduced synthesis of NO was implicated in alleviation of B stress in pepper plants.…”
Section: Introductionmentioning
confidence: 99%